Trapped active toy robots: theory and experiment. (27th May 2021) - Tapia-Ignacio, Cecilio; Gutierrez-Martinez, Luis L; Sandoval, Mario
Abstract: We characterise the diffusion, mean-square speed, mean-square angular displacement, radial and speed probability distributions of toy robots called 'hexbugs-nano' that move on a dish antenna (with added surface roughness) simulating a harmonic well. It is observed that a model considering the system's translational inertia but neglecting its moment of inertia, together with the inclusion of a constant external torque in the orientational motion, suffices to describe the robots' dynamics. Langevin dynamics simulation are also performed and a good agreement between theory, simulations and experiments is observed.